Brave new Bollywood : in conversation with contemporary Hindi filmmakers - Nirmal Kumar, 1964-; Chaturvedi, Preeti (New Delhi ; Thousand Oaks, California : SAGE Publications, 2015)
This book examines filmmakers in India, their religious beliefs, social moorings, cinematic influences, attitudes towards filmmaking and experiences of making movies.--Publisher's description.
Brave new world: an introduction -- Dibabkar Banerjee: Of milieu, technique and the dialetic of anti-dumb cinema -- Kiran Rao: the personal as the voyeur- the aesthetics of meaning -- Reema Kagti: collaboration and commerce-treading the thin line -- Zoya Akhtar: Urban and unapologetic-the cinema of Zoya Akhtar -- Shonali Bose: loss and survival-the cinema of meaning -- Anusha Rizvi: Content as king-how stories create filmmakers -- Onir: the politics at the margins-being an alternative filmmaker in Bollywood -- Tigmanshu Dhulia: the alternative as mainstream-blurring boundaries in cinematic tradition -- about the authors.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Motion picture producers and directors -- India -- Interviews; Motion pictures -- India; Motion pictures -- Production and direction -- India; Producteurs et réalisateurs de cinéma -- Inde -- Entretiens; Cinéma -- Inde; Cinéma -- Production et réalisation -- Inde; PERFORMING ARTS -- Reference; Motion picture producers and directors; Motion pictures; Motion pictures -- Production and direction; India; Interviews; Interviews